2013
DOI: 10.1111/jac.12027
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Development and Yield of Crambe Abyssinica Under Saline Irrigation in the Greenhouse

Abstract: Salinity is one of the major factors limiting agricultural productivity in arid and semi‐arid regions. Saline areas around the world are increasing and sources of fresh water are decreasing. The increasing importance of the use of brackish water to supplement regular irrigation has demonstrated a need for finding new potential plants with tolerance to irrigation with saline water which can be used in industrial agriculture. The aim of this study was to determine whether irrigation with brackish water of Crambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
1
21
0
4
Order By: Relevance
“…Regarding to soil salinity, it was necessary to transform the data in 1 x to EC; 1 x to Na; x to Mg and log (x) for Ca and Cl ( Table 3). (1: (1) Na (1) K Ca (2) Mg (3) P Al (4) O.M. (2) Salinity levels (N) 4 0.013 ns 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to soil salinity, it was necessary to transform the data in 1 x to EC; 1 x to Na; x to Mg and log (x) for Ca and Cl ( Table 3). (1: (1) Na (1) K Ca (2) Mg (3) P Al (4) O.M. (2) Salinity levels (N) 4 0.013 ns 0.…”
Section: Resultsmentioning
confidence: 99%
“…Crambe (Crambe abyssinica) is an oil plant of the cruciferous family native of the Mediterranean region from Ethiopia to Tanzania for ornamental purposes and with high economical value, especially in Central Asia and the Aral Sea region; however, it is cultivated in tropical and subtropical regions [4]. The literature is not abundant about the effects of salinity in crambe production, although it is believed that crambe has great potential to figure as raw material for biofuel, among the 40 oil species already known with this potential [5].…”
Section: Introductionmentioning
confidence: 99%
“…This result disagrees with that of Francois and Kleiman (1990), who found no effect of salinity on vegetative growth up to 8 dS m -1 . Ionov et al (2013) -planting Crambe Abyssinica seeds originated from the Aral Sea area in Uzbekistan -observed that water with up 3 dS -1 EC might be used in irrigation of crambe with no loss in seed yield. However, when water with 6 and 9 dS -1 EC was used, seed yield was significantly reduced in both years of the experiment, suggesting tolerance to moderate salinity levels (Ionov et al, 2013).…”
Section: Root Length Root Dry Matter and Shoot Dry Mattermentioning
confidence: 99%
“…Furthermore, effects of specific ions may involve direct toxicity or a variety of nutritional effects (Bernstein and Hayward, 1958). Salinity is one of the major factors limiting agricultural productivity in arid and semi-arid regions (Ionov et al, 2013). Irrigation has resulted in the accumulation of salts to above-normal concentrations in the rooting zone of arable land, as high rates of evaporation and transpiration draw soluble salts from deep layers of the soil profile (Rozema and Flowers, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation